Reassessing green exercise research: unveiling methodological gaps and pathways for progress - Luca Laezza; Luca Laezza; Stefano De Dominicis; Margherita Brondino (Frontiers Media S.A., 2024)
The present review critically assesses the nexus between physical activity, nature exposure and health benefits by analysing environmental measures in green exercise research. A Cochrane-inspired review of systematic studies exposes methodological gaps, emphasising the scarcity of long-term research and the lack of rigorous designed studies. It calls for more robust, varied research designs and improved environmental metrics. The findings advocate for longitudinal research to better comprehend the mental and physical health benefits of exposure to nature. Embracing an ecological-dynamic perspective is recommended to advance our understanding of the intricate connections between activity, environment, and well-being.